Plan de salvaguardia de los juegos tradicionales para la vigencia de las manifestaciones del patrimonio cultural inmaterial de la ciudad de Riobamba - Fiallos Pillapa, Cristina Alejandra (2018)
The present research work was made with the field´s application technique in order to see the lack of participation of the new generations in the practice of these games, the main objective was to design the “Plan of safeguarding the games for the validity of the intangible cultural heritage manifestations of the Riobamba city” In this research work surveys were conducted to the participants, as well as to the viewers of the games that was the universe object of study taking into account if they knew the games and the practice of them, in different aspects related to traditional games, they can give the real situation concerning their practice in our community and the way as they learned it. The relevant programs were made taking into account the low participation or new generations in the practice of traditional games, since they are a cultural identity of our country. Emphasis is placed on realizing a revaluation of its continuous practice by our children and youth to preserve the legacy of our people.